2009
DOI: 10.1161/strokeaha.109.556068
|View full text |Cite
|
Sign up to set email alerts
|

Medical (Nonsurgical) Intervention Alone Is Now Best for Prevention of Stroke Associated With Asymptomatic Severe Carotid Stenosis

Abstract: Abstract-Significant advances in vascular disease medical intervention since large randomized trials for asymptomatic severe carotid stenosis were conducted have prompted doubt over current expectations of a surgical benefit. In this systematic review and analysis of published data it was found that rates of ipsilateral and any-territory stroke (ϩ/ϪTIA), with medical intervention alone, have fallen significantly since the mid-1980s, with recent estimates overlapping those of operated patients in randomized tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
483
1
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(505 citation statements)
references
References 83 publications
6
483
1
15
Order By: Relevance
“…Earlier studies found the risk of stroke with asymptomatic carotid stenosis to be approximately 1.3% per year among patients with stenosis less or equal to 75%, and approximately 3.3% annually among patients with stenosis greater than 75% [35]. The "best" medical therapy has changed because the publications of clinical trials have compared carotid endarterectomy with medical therapy for asymptomatic carotid stenosis [36]. The risk of stroke associated with asymptomatic carotid stenosis has fallen significantly during the past 20 years [36,37].…”
Section: Modifiable Medical Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies found the risk of stroke with asymptomatic carotid stenosis to be approximately 1.3% per year among patients with stenosis less or equal to 75%, and approximately 3.3% annually among patients with stenosis greater than 75% [35]. The "best" medical therapy has changed because the publications of clinical trials have compared carotid endarterectomy with medical therapy for asymptomatic carotid stenosis [36]. The risk of stroke associated with asymptomatic carotid stenosis has fallen significantly during the past 20 years [36,37].…”
Section: Modifiable Medical Risk Factorsmentioning
confidence: 99%
“…The "best" medical therapy has changed because the publications of clinical trials have compared carotid endarterectomy with medical therapy for asymptomatic carotid stenosis [36]. The risk of stroke associated with asymptomatic carotid stenosis has fallen significantly during the past 20 years [36,37]. With contemporary medical therapy, the average annual rate of ipsilateral stroke is estimated to be <1%.…”
Section: Modifiable Medical Risk Factorsmentioning
confidence: 99%
“…The stroke counteractive action viability of medicinal treatment alone (reassuring a sound way of life and suitable utilization of medication) has enhanced by no less than 80% since the randomized trials of CEA versus restorative treatment began [6][7][8][9]. The perception of wager ter results now in patients with ACS without procedural mediation and its suggestions for patients with SCS (counting the requirement for better patient determination and more tightly periprocedural stroke and passing rate principles) have barely affected on rule proposals.…”
Section: Casmentioning
confidence: 99%
“…Current rules frequently underutilize and underestimate quality, freely approved, non-randomized observational information. Such information, for instance, have demonstrated enhanced patient results with restorative treatment alone [6][7][8][9] and with CEA, [10][11][12] and a determination of significantly higher dangers from CAS [2,3].…”
Section: Casmentioning
confidence: 99%
“…There is paucity of data as to the exact annual risk of stroke in patients with asymptomatic carotid stenosis on modern medical therapy. By 1 estimate, the annual risk of stroke has dropped significantlyto <1% per year with medical therapy alone, raising serious questions as to the benefit of any revascularization procedure [45]. Spence et al [46] have shown that transcranial Doppler can identify a subgroup of patients with asymptomatic stenosis who have microembolic signals that are at higher risk for stroke than those who do not have these microembolic signals.…”
Section: Carotid Endarterectomy For Asymptomatic Carotid Stenosismentioning
confidence: 99%